Red de conectividad en la cuenca del río Santiago: un modelo innovador para contribuir al cierre de la brecha digital en el marco de las Alianzas Multiactor - Paco Fernández, Juan Antonio (2024)
This article describes the technical characteristics and performance tests of the broadband wireless network implemented in the Santiago River basin (Amazon Region - Peru). It also details the context and the process of inter-institutional coordination in which this project has been developed. Within the framework of a broad initiative led by the Peruvian National Government, a collaboration process was carried out between public and private actors and academia for the development of the province of Condorcanqui (Amazon Region - Peru). From this process, various studies and projects emerged, including the design and implementation of a connectivity solution for the Santiago River basin (Amazon Region - Peru). The implementation of the network seeks to complement the plans and projects that the State has regarding the expansion of connectivity and telecommunications services to close the digital divide in Peru, through an unconventional technical proposal. The main result of this project’s execution, and the corresponding process, is the validation of a proof of concept for an innovative articulation model that seeks to combine the efforts of public and private actors to reduce the digital divide in isolated rural communities with sparse and dispersed populations. Furthermore, the sustainability of this deployment also follows an innovative model involving a telecommunications service operator and promoting Internet access by public institutions in the Health and Education sectors present in the Santiago River basin. It yields complementary results, such as the training of public employees and the strengthening of the services provided by public institutions through the delivery of medical and computer equipment.